DEVELOPMENT OF A COMMUNITY LEARNING ACTIVITY CENTER (PKBM) BASED ON THE POTENTIAL OF LOCAL NATURALS TO IMPROVE THE ABILITY OF COMMUNITY GREEN BEHAVIOR - Nursaidah, Enden; Rosita, Tita; Mulyono, Dinno (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2020)
The Community Learning Activity Center (PKBM) as an institution formed by the community in aneffort to empower the community should be a solution tool in developing various development needs,demands and harmonizing with the local natural potential of the local community. This is related to thedevelopment of attitudes related to local wisdom and optimal empowerment of available localpotentials. Humans and nature are two things that cannot be separated. Both are interrelated and willalways need each other. As a center for information and community empowerment through education,PKBM needs to be developed as a center for activities that teach the community not only about theutilization of local natural potentials but on empathetic attitudes towards the natural environment. Thisis to maintain sustainability for both humans and nature as an agenda for education for sustainabledevelopment. This article will explain an example of PKBM development that applies learning activitiesbased on the local potential of nature to develop the green behavior of local communities.